#TITLE_ALTERNATIVE# - JUNAIDI FIRMANSYAH (NIM: 15108094); Pembimbing: Dr. techn. Dudy D. Wijaya, ST. M.Sc.; Dr. Ir. Dina,
The ionosphere affects the propagation of electromagnetic waves in the form of time delay. The ionospheric effects are the main source of error in positioning and navigation using GPS with the value can reach up to tens meters. To obtain a very precise position, the effects should be eliminated. The magnitude of the effects depends on Total Electron Content (TEC) and the frequency. Therefore, a study of the ionosphere characteristic is very important. Receiver Code Bias (RCB) is also needed for estimating the TEC. RCB is a bias from receiver equipment.The aim of this research is to study the characterisitic of the ionosphere, focusing on the spatial variation of VTEC (Vertical Total Electron Content) using method of data code in Java. BIG, Jepara, Cirebon, Semarang, Purbalingga, and Magelang stations were used in this research. Characteristic of VTEC were seen by the daily, seasonally and averaged difference of VTEC among GPS observation stations.The result of data processing showed that the highest ionospheric effects occurred during the equinox season with VTEC values over all stations reaching more than 60 TECU, while the lowest was in summer solstice season with VTEC values of more than 50 TECU. The value of the VTEC difference would be larger if the straight distance among the stations and the difference in latitude is higher. The RCB results also affected the VTEC estimation with VTEC values given were twice the value of RCB.